Naik ke Sorga, Duduk di Sebelah Kanan Allah Bapa yang Mahakuasa: Suatu Tinjauan Teologis-Dogmatis terhadap Rumusan Pengakuan Iman Rasuli Alinea 2 - Sisco Turnip, Ricardo; Humala Pakpahan, Jordan; Fasius Banjarnahor, Irsanto Boni; Sri Sinaga, Dewi (Attractive : Innovative Education Journal, 2021)
The purpose of this research is to understand the Biblical and Theological basis for the meaning of the sentence "ascended to heaven, sitting at the right hand of God the Father" based on the Apostles' Creed by looking at the Bible verses that refer to this sentence as the basis of the Bible in delivering its theological meaning, and understand the meaning and meaning of "ascended into heaven, sitting at the right hand of God the Father" in the Apostles' Creed, which is a formulation of a confession of faith that contains history, as a confession of the church's faith in the Triune God. The research methodology used is the Library Research method, using literature or literature that supports the title that has been put forward, where the author will use literature regarding Christian dogma, history related to the formulation of the Apostles' Creed, and other literature that supports the author's thinking references. The results and conclusions that can be drawn are that the Christian confession of faith formulated in existing confessions of faith such as the Apostles' Creed is certainly needed as a guide to the church's faith in witnessing and proclaiming its testimony to God who reveals His love in His Trinity. So the church has the task of confirming the faith of its members through testimony in the teachings that the church provides to its congregation. Teachings about Jesus Christ are contained in the HKBP Confession and Martin Luther's Catechism as documents used by the HKBP church. Keywords: Biblical and Theological, Theological Meaning